Disruptive Behavior Programs on Primary School Students: A Systematic Review - Diego Martín Retuerto; Iker Ros Martínez de Lahidalga; Irantzu Ibañez Lasurtegui (MDPI AG, 2020)
The objective of this study was to review the existing international literature on research and programs for the reduction of disruptive behavior in primary school students. For this purpose, according to PRISMA-ScR, a mixed systematic review was performed in six databases in order to obtain wide and extensive information related to the subject under study. The studies obtained were analyzed through a table which emphasized the data related to: Author(s), year, educational stage, location, objectives, instruments, and results. As for the selection of studies, the UNESCO Thesaurus and the ERIC Thesaurus terminology was used. In addition to specifying the search for studies performed between 2004 and 2020 (both inclusive), articles written in Spanish and English were selected. Furthermore, in a final phase among the articles analyzed, those that were not or did not contain intervention programs were discarded. Therefore, a total of thirty-five articles out of more than twenty thousand were analyzed in depth. The results showed that a majority of programs were implemented in the primary education stage, as well as a predominance of the use of instruments, such as questionnaires and observation charts. In addition, it is important to underline that 77.14% of the programs analyzed were effective, hence, they met the proposed objectives. In summary, although the number of intervention programs for the reduction of disruptive behavior that can be found in the international scientific literature is growing, there is still a long way to go in order to create a large network that can serve as a foundation for interventions in primary education students.